Evaluation of mistakes in breaststroke swimming - Kapus, J.; Stibilj, J.; Muha, K. K. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
Competitive swimming is based on times achieved for a selected swim distance. Therefore, quantitative analysis is most commonly used by swimming coaches. In addition to measuring swim times, they are usually determined by measuring stroke rate, stroke length, stroke index, index of coordination as well as breathing frequency. In addition, methods of quantitative analysis may include video-based techniques from which kinematics and kinetics can be derived by direct measurements of velocity and force using various velocity and force measurement devices (Sanders et al., 2006). However, in some cases, a quantitative approach may not reflect progress in the athlete's swimming technique. In fact, feedback from a coach to a swimmer is often based on qualitative observations. Swimming coaches perform technique analysis themselves by observing and qualitatively evaluating. The latter is based on their own knowledge and experience (Lees, 2002). They need to identify the technique mistakes and evaluate them in terms of their impact on the swimmer's performance. For this reason, there is a clear need for an assessment tool that can help swimming teachers and coaches in their work with swimmers of different quality levels. In this regard, it is surprising that the researches of Pion et al. (1988), Stibilj et al. (2020) and Kapus et al. (2022) were, to our knowledge, the only attempts to date to evaluate a swimming technique, i.e. breaststroke and backstroke, respectively, using an mistakes rating. Therefore, we sought to identify the perceptions of experienced swimming teachers and coaches regarding common mistakes in breaststroke swimming. In addition, we compared their perceptions with those of participants who have no professional experience teaching/coaching swimming. Finally, we attempted to develop a breaststroke assessment tool (BrAT).